2001
DOI: 10.1243/0954406011520643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of misalignment on the transmission characteristics of magnetic couplings

Abstract: Magnetic couplings possess no mechanical contact and permit higher assembly tolerance for transmitting torque from a primary driver to a follower by magnetic force. This paper investigates the eVects of misalignment on the transmission characteristics of synchronous magnetic couplings. The misalignment can be categorized into the following three types: transverse, angular and a combination of these two misalignments. Without loss of generality, an axial synchronous magnetic coupling is adopted in the present b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The results of each model, which were maximal coupling torque of PMC, were summarized in Table II in next subsection. The maximal torque is yielded when the twisted angle is half‐a‐pole pitch (Huang et al , 2001).…”
Section: Analysis and Experimentsmentioning
confidence: 99%
“…The results of each model, which were maximal coupling torque of PMC, were summarized in Table II in next subsection. The maximal torque is yielded when the twisted angle is half‐a‐pole pitch (Huang et al , 2001).…”
Section: Analysis and Experimentsmentioning
confidence: 99%
“…However, magnetic fields are never perfectly balanced and will always cause assemblies to shift to the lowest energy state. Consequently, all magnetic couplings require full mechanical support through radial and thrust bearings (Huang, Chen, Yau, & Sung, 2001;Wallace, Wohlgemuth, & Lamb, 1995;Yonnet, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Prabhakar et al [15] analyzed the transient response of a misaligned rotorcoupling-bearing system passing through the critical speed using the finite element method for flexural vibrations and found that the subcritical speeds at one-half, one-third, and one-fourth of the critical speed. The mathematical model constructed for the effect of misalignment on magnetic coupling [16] derived a set of nonlinear equations for parallel misalignment effect [17] between two rotating shafts and two rotor segments with angular misalignment [18]. Extensive experimental studies were made by researchers [19][20][21][22][23] on unbalance and misalignment [24,25], misaligned rotorball bearing systems [26,27], rigidly coupled rotors [28,29], and pointing complexity of diagnosis for misalignment and unbalance using vibration analysis.…”
Section: Introductionmentioning
confidence: 99%